2020
DOI: 10.3389/fendo.2020.00256
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Incidental Findings in 403 Taiwanese Girls With Central Precocious Puberty at Initial Diagnosis

Abstract: Background: Whether girls with central precocious puberty (CPP) should undergo routine brain magnetic resonance imaging (MRI) to identify potential intracranial pathologies is controversial. Aims: To evaluate the brain MRI results of girls with CPP and identify the clinical and endocrine predictors of brain abnormalities. Methods: This retrospective study obtained data from pediatric endocrine clinics at Chang Gung Children's Hospital. From 1997 and 2017, 403 girls were consecutively diagnosed with CPP. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
2
22
1
Order By: Relevance
“…According to recent literature [ 6 , 7 ], brain insults were classified into 3 groups as determined in Table 1 . In total, 44 girls with CPP (17.1%) had brain lesions, of which 34.0% (n=15), 38.6% (n=17), and 27.4% (n=12) presented pathological findings, brain lesions with questionable relationships to CPP, and incidental findings, respectively ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent literature [ 6 , 7 ], brain insults were classified into 3 groups as determined in Table 1 . In total, 44 girls with CPP (17.1%) had brain lesions, of which 34.0% (n=15), 38.6% (n=17), and 27.4% (n=12) presented pathological findings, brain lesions with questionable relationships to CPP, and incidental findings, respectively ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Routine cranial MRI scans are recommended for girls younger than 6 years of age because it is necessary for the early diagnosis of brain tumors and progressive pathologies of CPP. However, the prevalence of hypothalamic hamartoma in children with organic CPP aged 0–6 years was low (0.4%) [ 7 ]. Noteworthy, Yoon et al [ 8 ] found that none of 317 South Korean girls aged 6.9±1.6 years with CPP had pathological brain lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Pineal cyst and Rathke cyst were detected by MRI in three of our patients. Recently, the prevalence of pineal cyst (0.8%) and Rathke cyst (2%) have been reported in 251 girls with CPP [ 22 ]. One conceivable explanation is that a cyst somewhat abrogates the normal prepubertal gonadotropin inhibition [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A B Hansen and others Sex steroids in adolescencel https://eje.bioscientifica.com since NF-1 can be a cause of intracranial tumors related to CPP (26). Factors arguing against brain MR are onset of PP over the age of 6 years and some ethnic groups who have a tendency toward early normal puberty including internationally adopted children, as patients with such factors are more likely to present with ICPP and no intracranial pathology (26,27,28).…”
Section: :1 R21 Reviewmentioning
confidence: 99%